Native Italian poultry products: the factors influencing consumer perceptions - Eleonora Erika Cappone; Valeria Zambotto; Jatziri Mota-Gutierrez; Dominga Soglia; Giulia Maria Daniele; Marta Cianciabella; Andrea Pieroni; Renata Soukand; Mauro Penasa; Arianna Buccioni; Margherita Marzoni; Nicolaia Iaffaldano; et al. (Italian Journal of Animal Science)
Utilisation and conservation of native chickens are fundamental for sustainable poultry production. This study aimed to predict the key factors influencing consumer perceptions of the quality traits of products from native poultry breeds and their willingness to pay for them. In addition, consumer preferences for native chicken meat and eggs were compared with those from commercial lines. A generalised linear mixed model was used to analyse responses from 1488 Italian consumers. Age, willingness to pay, the perceived productivity of native breeds, and chicken meat and egg preferences in terms of the rearing system were the main predicting factors influencing the importance consumers placed on the geographical proximity and the perceived quality traits of poultry products from native breeds. Younger people and price-sensitive consumers appeared to be more concerned about the food safety aspects of eggs from local breeds. Those perceiving Italian native breeds as more productive than commercial lines placed greater importance on the geographical proximity and perceived native breed chicken meat to be of superior nutritional composition. Price-sensitive consumers also associated chicken meat from local breeds with a higher cholesterol content. Our findings suggest that the quality traits investigated in the present study correlated positively with each other and positively influenced willingness to pay a higher price for native poultry products. These results demonstrate the importance of consumer education to encourage informed choices in favour of sustainable poultry farming, thereby fostering economic development, environmental sustainability, cultural preservation and consumer satisfaction.